2021
DOI: 10.1115/1.4050629
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Laminar-Turbulent Transition on a Low-Pressure Turbine Outlet Guide Vane

Abstract: This work presents an experimental and numerical investigation on the laminar-turbulent transition and secondary flow structures in a Turbine Rear Structure (TRS). The study was executed at engine representative Reynolds number and inlet conditions at three different turbine load cases. Experiments were performed in an annular rotating rig with a shrouded low-pressure turbine upstream of a TRS test section. The numerical results were obtained using the SST k–ω turbulence model and the Langtry- Menter γ–θ trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Because of their function, OGV have to straighten the fan and are subject to stresses from laminar and turbulent flows of hot air at high pressure and the particles (dust, sand) and water droplets they carry away. [10][11][12] Parts can also be exposed to various aeronautical fluids in the engine during normal use or by accident. Jet fuel, hydraulic fluids and de-icing fluids cause irreversible chemical modifications to metal parts 13,14 or FRP composite parts.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their function, OGV have to straighten the fan and are subject to stresses from laminar and turbulent flows of hot air at high pressure and the particles (dust, sand) and water droplets they carry away. [10][11][12] Parts can also be exposed to various aeronautical fluids in the engine during normal use or by accident. Jet fuel, hydraulic fluids and de-icing fluids cause irreversible chemical modifications to metal parts 13,14 or FRP composite parts.…”
Section: Introductionmentioning
confidence: 99%
“…For more information on diffusion rates, please refer to the original source [11]. A recent study [12] aimed to analyze the heat transfer and transition predictions of the γ − Re θ model in a low-pressure turbine stage. The results suggested that the model could predict the spanwise distribution of transition onset.…”
mentioning
confidence: 99%